US GEOPOLITICAL INTERESTS AND REGIONAL SECURITY IN CENTRAL ASIA - ZHOLBARYSSOVA, Assel (Studia Universitatis Babes-Bolyai Studia Europaea, 2018)
This article is aimed at developing and analyzing the strategic concerns of the main geopolitical powers in the Central Asian region. The author concludes that the specialty of the Central Asia is a beneficial geopolitical location and great amount of nature resources that makes the region an object of world powers’ geopolitical interests. The main actors in the Central Asia are Russia, China and the USA. They have an influence on political processes inside of the region, realizing their own strategies.